2015
DOI: 10.1080/10410236.2014.936337
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Sociocultural Barriers to Mammography Adherence Among Appalachian Kentucky Women

Abstract: Despite lower breast cancer incidence rates, Appalachian women evidence lower frequency of screening mammography and higher mortality risk for breast cancer compared to non-Appalachian women in Kentucky, and in the United States, overall. Utilizing data from 27 in-depth interviews from women in seven Appalachian Kentucky counties, this study examines how Appalachian women explain sociocultural barriers and facilitators to timely screening mammography, and explores their common narratives about their mammograph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…Specifically, we compared expansion status based on Appalachia status. Prior studies have shown that women in Appalachia regions have much lower breast cancer screening rates and significantly higher mortality rates compared to the national average, 11,16 although none of the prior studies have evaluated the role of ACA expansion in this region. Second, the analysis evaluated differences in screening rates by pre- and post-expansion status.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Specifically, we compared expansion status based on Appalachia status. Prior studies have shown that women in Appalachia regions have much lower breast cancer screening rates and significantly higher mortality rates compared to the national average, 11,16 although none of the prior studies have evaluated the role of ACA expansion in this region. Second, the analysis evaluated differences in screening rates by pre- and post-expansion status.…”
Section: Discussionmentioning
confidence: 99%
“…The National Cancer Institute recognizes the Appalachia region of the United States as a special priority area, given that it represents one of the most economically disadvantaged, and medically underserved regions in the United States. 7 -10 Several factors have been identified that may explain later stage at diagnosis and higher breast cancer mortality observed among women living in the Appalachian regions of the United States, 11 -13 including lower socioeconomic status and lack of access to health care, 9,14,15 lower prevalence of routine mammography, and a lower likelihood to receive recommended treatment for breast cancer. 16 -18…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Multiple researchers were used to ensure sampling reliability. Working independently, two coders descriptively assessed the database (Cohen, Wilson, Vanderpool, & Collins, 2015). Two meetings were held to review interpretation, discuss discrepancies, and arrive at mutual consensus (Campbell & Wallace, 2015; Cohen et al, 2015).…”
Section: Methodsmentioning
confidence: 99%
“…Working independently, two coders descriptively assessed the database (Cohen, Wilson, Vanderpool, & Collins, 2015). Two meetings were held to review interpretation, discuss discrepancies, and arrive at mutual consensus (Campbell & Wallace, 2015; Cohen et al, 2015). In the case of any ambiguity with regard to the description of the situation (e.g., victim type, actions, charges), we conducted an Internet search for published information regarding the incident that could clarify information about the victim and offer more details about the interaction (i.e., current and former romantic partners vs. strangers).…”
Section: Methodsmentioning
confidence: 99%